KUALITAS BAKTERIOLOGIS AIR MINUM ISI ULANGPADA TINGKAT PRODUSEN DI KABUPATEN BADUNG. - Partiana, Made; Sudiana Mahendra, Made; Redi Aryanta, Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2015)
The presence of refill drinking water in the urban community especially Badung Regency is favored as an alternative of water supply because it cost relatively cheaper compared to water in pacage. The number of samples in this study was 45 outlets with refill drinking water as its study material. The bacteriological examination of the material of study was done on included most probable number (MPN) of coliform and Eschericia coli . The result of refill drinking water investigation bacteriological examination revealed 88.9 % outlets were considered qualified, 11.1 % of them were unqualified because they contained coliform bacteria and one stall had Eschericia coli . The observation hygiene 15.6 % unqualified and sanitation outlets examination 17.8 % unqualified. Correlation test showed no significant relationship between raw materials, equipment, processing, hygiene and sanitation autlets with bacteriological quality of drinking water
Keywords: Refill drinking water; Hygiene Sanitation; Bacteriological Quality